Integrasi Kebijakan Pengelolaan Lingkungan dan Pembangunan Berkelanjutan di Kota Jayapura - Annisa Fitriah Mudassir; Muhammad Khaidir Kahfi Natsir (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This paper discusses the integration of environmental management policies and sustainable development in the city of Jayapura, which is an important city in Indonesia with a rich diversity of natural resources and significant environmental challenges. The issues raised pertain to the necessity of understanding and implementing a holistic approach to policies that integrate environmental aspects into the regional development process. This research aims to explore the relationship between environmental management policies and sustainable development, as well as to identify the legal principles underlying environmentally sustainable management in Jayapura. The methods used in this study include a normative legal approach and empirical analysis with descriptive analysis, encompassing literature studies and data collection from various sources, including policy documents, interviews with stakeholders, and field observations. The findings indicate that despite the existence of a supportive legal framework, such as the Environmental Management Law and local policies, challenges in the implementation of environmental policies in Jayapura remain significant. Pollution, ecosystem degradation, and conflicts between land use for development and environmental preservation are critical issues that need to be addressed. Furthermore, this research finds that community participation in environmental management is crucial for achieving sustainable development goals. Local communities need to be involved in the decision-making processes to ensure that the policies adopted are not only economically beneficial but also consider environmental sustainability and social welfare. The conclusion drawn is the need for continuous evaluation and oversight of environmental policies, as well as strengthening community capacity in natural resource management. Thus, effective integration of environmental management policies can be achieved, ultimately supporting inclusive and sustainable development in the city of Jayapura.